خصائص اللغة الشعرية في ديوان لؤلؤة في القلب لفاروق شوشة - فريجات, رقيعة, زينب عبير; تامة, منى (University of El-oued, 2022)
أن اللغة العرية تهدف أو تسعى إلى اخراج مكبوتات الشاعر العاطفية والوجدانية وبثها في نفس المتلقي وذلك من خلال مجموعة من الخصائص والتي تميزت بها اللغة الشعرية ولعل من أهمها: الاختلاف، المفارقة، الارتباط، الانحراف، النسيج الايقاعي، خصوصية التركيب، التصوير، الانفعالية، الغموض. ومن الأساليب التي حضيت بها اللغة الشعرية في ديوان لؤلؤة في القلب لفاروق شوشة نجد أسلوب التقديم والتأخير والحذف. وقد اهتم شوشة في ديوانه على جمالية الصورة الشعرية والتشبيهية والاستعارية. كما اهتم بالصورة التراسلية ومزج بين مجموعة من الحواس كما نجده أيضا قد مزج بين شكلي القصيدة فمرة يكتب بالشكل الحديث ومرة أخرى بالشكل القديم للقصيدة. The naked language aims or seeks to bring out the poet's emotional and sentimental repressions and broadcast them in the same recipient through a set of characteristics that characterized the poetic language, perhaps the most important of which are: difference, paradox, association, deviation, rhythmic texture, privacy of installation, photography, emotionality, ambiguity . One of the methods in which I mastered the poetic language in Farouk Shousha'sDiwanLulu'a fi Al Qalb is the method of introduction, delay and omission. In his poetry, Shousha focused on the aesthetic of poetic, simile and metaphorical images. He also paid attention to the correspondent image and mixed a group of senses. We also find that he mixed the two forms of the poem, once written in the modern form and again in the old form of the poem.
Keywords: خصائص اللغة الشعرية ، ديوان لؤلؤة في القلب، فاروق شوشة; Characteristics of the poetic language in Farouk Shousha'sDiwan, "A Pearl in the Heart".